2020
DOI: 10.1038/s41416-020-0971-y
|View full text |Cite
|
Sign up to set email alerts
|

Mac-2-binding protein glycan isomer enhances the aggressiveness of hepatocellular carcinoma by activating mTOR signaling

Abstract: Mac-2-binding protein glycan isomer enhances the aggressiveness of hepatocellular carcinoma by activating mTOR signaling (Mac-2結合蛋白糖鎖修飾異性体はmTORシグナル伝達経路を活性化することにより肝細胞癌の悪性度を増悪させる) Background: Liver cancer is the fourth leading cause of cancer-related death worldwide. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, mostly occurs in people with liver cirrhosis. For HCC patients with severe liver fibrosis, treatment option is limited. Therefore, deeper understanding of HCC in fibroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
3
28
0
Order By: Relevance
“…Therefore, our aim was next to investigate the role of Gal-3 in progression of ICC cells and relevant regulatory mechanisms, which may shed some light on potential applications of Gal-3 in treating ICC. Accumulating evidence indicates that high expression of Gal-3 is associated with the development of various malignancies ( Dolgormaa et al, 2020 ; Li et al, 2020 ). In our study, the expression data of Gal-3 in ICC were retrieved from the TCGA database, and its correlation with the clinical stages of ICC was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our aim was next to investigate the role of Gal-3 in progression of ICC cells and relevant regulatory mechanisms, which may shed some light on potential applications of Gal-3 in treating ICC. Accumulating evidence indicates that high expression of Gal-3 is associated with the development of various malignancies ( Dolgormaa et al, 2020 ; Li et al, 2020 ). In our study, the expression data of Gal-3 in ICC were retrieved from the TCGA database, and its correlation with the clinical stages of ICC was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic stellate cell activation causes an increase in mechanical intrahepatic resistance and contributes to the development of portal hypertension. Furthermore, a study by Dolgormaa et al showed that M2BPGi was detected in cirrhotic liver stromal cells and enhanced the growth of HCC through the galectin-3/mTOR signaling pathway [24]. These mechanistic studies provide the pathophysiologic basis that supports the clinical utility of M2BPGi in cirrhosis.…”
Section: Discussionmentioning
confidence: 87%
“…In our previous study, we reported that M2BP mRNA is detected in the stroma of the fibrotic liver rather than in hepatocytes, 12 but M2BP, as the main component of M2BPGi, is the secreted glycoprotein 13 . M2BP mRNA is barely expressed in the normal liver but is upregulated in the fibrotic liver 14,15 .…”
Section: Introductionmentioning
confidence: 92%